The effect of nutrition education based on PRECEDE model on iron deficiency anemia among female students - Ali Khani Jeihooni; Sanaz Hoshyar; Pooyan Afzali Harsini; Tayebeh Rakhshani (BMC, 2021)
Abstract Background Iron deficiency anemia disrupts the concentration of adolescent girls; reduces their academic achievement, productivity, and physical strength, and increases the risk of infection. This research aim was to evaluate the effectiveness of the PRECEDE model nutrition education on iron deficiency anemia among female students of Fasa City, Fars Province, Iran. Methods This quasi-experimental study was done on 160 students (80 experimental and 80 control groups) who were selected using a random sampling method in Fasa City, Fars Province, Iran, in 2018-2019. The educational intervention included six sessions based PRECEDE model for 45 or 50 min. A scale of this study consisted of two parts; demographic information, and PRECEDE constructs were used to determine the nutritional behaviors status concluding preventing iron deficiency anemia and hemoglobin, hematocrit, and ferritin blood level in two (before and 4 months after intervention) times. Results In the experimental group of the students the mean age was 13.85 + 1.72 years and in the controlled group was 13.60 + 1.81 years. Moreover, there was no significant difference in the PRECEDE constructs, and nutritional behaviors preventing iron deficiency anemia before the intervention in two groups of study. However, the experimental group showed a significant increase 4 months after the intervention. Also, there was no significant difference in the mean score of hemoglobin, hematocrit, and ferritin blood level between the two groups before the intervention. However, in ferritin level, a significant increase was shown in 4 months after the intervention in the experiential group. Conclusions Based on results, the nutrition intervention education base on PRECEDE model has a positive effect to improve iron deficiency anemia preventive behaviors in female students.